KILAS BALIK EKONOMI ISLAM DI INDONESIA - Musfiqoh, Siti (El-Qist: Journal of Islamic Economics and Business (JIEB), 2011)
The historical development of Islamic system economic in Indonesia reflects the dynamics of the aspirations and wishes of the Indonesian people themselves, to have an alternative fair economic system, in the real sector. as an alternative search process in the monetary system which is characterized by the principles of transparency, fairness, balance and ethics in creating a prosperous society materially and spiritually. The initial of this alternative search system, initiated by scientific studies about Islamic economic and financial. The result of those studies is the publication of islamic banking laws. The initial of Islamic economic system of banking began in the early 1980's, when the government issued a policy package on Banking liberalization.The scholars' at that time established an interest-free rate, bank Muamalat (Islamic banks) at the end of 1991 and operational in early 1992, but none of the legal device that can be used as a reference.This condition lasted until the year 1997, in which Indonesia was hit by the economic and moneter crisis.At that time, when conventional banks had been liquidated, , Islamic banks showed their existence and do not experience economic shocks. Aspiration of Indonesian people had been growing to have an Islamic financial institutions, non bank financial institutions and the banking through the application of system for a favorable outcome for the customer and the bank. Furthermore, the trial conducted by the public along with academics and practitioners to realize and practice the idea of monetary systems ranging from small-scale enterprises both bank and non bank financing are trying to apply the concept of revenue sharing. At this stage, the establishment of Islamic banks are seen as an indicator of economic progress is happening in Islamic economic, so almost society equate Islamic Economic with Islamic banks, or non-bank sharia financial institutions other. Though the scope of Islamic economics is much broader than just a Sharia finance. It covers macroeconomic concepts, micro-economic, fiscal, monetary, and also the much concept of economic development policies and instruments with all the variables.